Improving EFL Students' English Language Skills through Utilizing Trending Palestine Content: A Content-Based Instruction Approach at STAI YDI Lubuk Sikaping - Endila, Wahyuni; Mei, Nining Yus; Maimori, Romi; Defrinal, Defrinal; Gusmanedi, Randa (STBA Prayoga Padang, 2025)
EFL students' interest in learning English is declin in cause of some of curriculum such as IELTS and TOEFL preparation, incoherence the student doesn’t understand the concept and correct pronunciation from native speakers. The habit of using gadgets and watch and paly the digital content in their such time may cause the challenge to use some media as learning tools. This research purpose to improve the English language skills of students in major of Islamic Religious Studies and Islamic Broadcasting Communication at STAI YDI through using the trending Palestine-themed content with a Content-Based Instruction (CBI) approach. The research method employed was Classroom Action Research with 30 students as subjects. Data were collected through pre-tests and post-tests, observations, interviews, and analysis of students' writing assignments. The Results performed us the significant producing and increasing of vocabulary, reading comprehension, and speaking skills used by the student. The analysis of students' written work showed us the sentence structure abilities and vocabulary in the student writing. The CBI approach with trending content provided high learning motivation and authentic context. This research recommends using current content as a medium for EFL English language learning to effectively and holistically improve language skills. Keywords: Content-Based Instruction, English language skills, trending content, Palestine, learning motivation, EFL students